Over 12 Years Single Institutional Experience Performing Percutaneous Hepatic Perfusion for Unresectable Liver Metastases - Michael J. Carr MD, MS; James Sun MD; Jonathan B. Cohen MD; Jinhong Liu MD; Andrew A. Serdiuk DO; Stephen R. Stewart CCP; Navin Doobay CAA; Andrew Duclos CRNA; David A. Seal CRNA; Junsung Choi MD; Jonathan S. Zager MD (Cancer Control, 2020)
Patients with unresectable hepatic metastases, from uveal or ocular melanoma, are challenging to treat with an overall poor prognosis. Although over the past decade significant advances in systemic therapies have been made, metastatic disease to the liver, especially from uveal melanoma, continues to be a poor prognosis. Percutaneous hepatic perfusion (PHP) is a safe, viable treatment option for these patients. PHP utilizes high dose chemotherapy delivered directly to the liver while minimizing systemic exposure and can be repeated up to 6 times. Isolation of the hepatic vasculature with a double-balloon catheter allows for high concentration cytotoxic therapy to be administered with minimal systemic adverse effects. A detailed description of the multidisciplinary treatment protocol used at an institution with over 12 years of experience is discussed and recommendations are given. A dedicated team of a surgical or medical oncology, interventional radiology, anesthesiology and a perfusionist allows PHP to be repeatedly performed as a safe treatment strategy for unresectable hepatic metastases.